All ketchup, no mustard! - Tharp, Jason (Tharp, Jason. Nugget and Dog., 2021)
When a spicy mustard packet tries to make everyone grumpy, friends Nugget, a chicken nugget, and Dog, a hot dog, come to the rescue by starting a K.E.T.C.H.U.P. club to fight back with kindness.